2019
DOI: 10.1111/jpr.12246
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Essentialism at the Explicit and Implicit Levels: The Unique Status of Social Categories

Abstract: Psychological essentialism refers to a naive theory concerning fundamental elements that bring a category into its existence. The present study examined the structure of this lay theory as well as its implicitness, with a special focus on social categories. In Study 1, Japanese college students rated a number of categories that were natural‐kind, social, or human artifacts, in terms of different elements of essentialist beliefs. A factor analysis revealed that entitativity and naturalness are the common underl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
0
8
0
Order By: Relevance
“…Although essentialist beliefs about social categories have been demonstrated in a variety of cultures (22,23,24,12,25,26,27), there has been almost no comparative work on cultural differences in social category essentialism. One exception is a small number of studies on cross cultural differences in the development of essentialist beliefs (28,29,24).…”
Section: Significancementioning
confidence: 99%
See 2 more Smart Citations
“…Although essentialist beliefs about social categories have been demonstrated in a variety of cultures (22,23,24,12,25,26,27), there has been almost no comparative work on cultural differences in social category essentialism. One exception is a small number of studies on cross cultural differences in the development of essentialist beliefs (28,29,24).…”
Section: Significancementioning
confidence: 99%
“…First, the past literature on social essentialism is largely concentrated on western samples, the majority of which come from European, American and Australian populations. Given the limited evidence from eastern societies (27), the current study contributes to our understanding of social essentialist thinking more broadly by examining the phenomenon comparatively in China and the US. This allows us to examine essentialist thinking about social categories in two cultures that differ more than those examined in Study 1.…”
Section: Studymentioning
confidence: 99%
See 1 more Smart Citation
“…The first thing to note about the studies mentioned above is that they surveyed participants on their explicit, self-reported, beliefs about race. Various studies have found that when it comes to implicit attitudes about race (and other social categories), people tend to be more essentialist in their thinking (e.g., see Chas et al, 2018;Goff et al, 2008;Karasawa et al, 2019).…”
Section: Explaining Variation In Essentialist Thinkingmentioning
confidence: 99%
“…Karasawa, Asai, and Hioki's () study, entitled “Psychological Essentialism at the Explicit and Implicit Levels: The Unique Status of Social Categories,” is about psychological essentialism. This is the idea that we humans tend to perceive commonalities among category members, such that infants categorize living things (e.g., dogs and fish) together and differentiate artifacts (e.g., chairs and buildings).…”
mentioning
confidence: 99%